STRATEGI PEMERINTAH DESA PADA PENCAPAIAN STATUS DESA MANDIRI DI DESA JIMBAR KECAMATAN PRACIMANTORO KABUPATEN WONOGIRI - Annastasya, Fenta; Ngabiyanto; Tijan; Seftyono, Cahyo (Inisiasi, 2024)
The aim of this research is to examine and describe the strategy of the Jimbar Village Government and the obstacles faced as well as solutions to achieving independent village status.The method used in this research uses a qualitative method with a descriptive approach. The research location is on Jl. Pracimantoro-Jimbar KM.7 Jimbar Village, Pracimantoro District, Wonogiri Regency. Data collection techniques used in this research were interviews and documentation. The focus of this research is to describe strategies, obstacles and solutions for achieving independent village status in Jimbar Village. In testing the validity of the data used, source triangulation and technical triangulation were used. Meanwhile, the data analysis technique uses the qualitative analysis technique through the stages of data collection, data reduction, data presentation and drawing conclusions.The results of the research show that the strategy carried out by the Jimbar Village Government to achieve independent village status is carried out through strategies including: first, the preparation of six-year medium-term goals for the Village RPJM and realizing them through the Village RKP each year through the Village APBDes; second, implementing the Village RPJM strategy through IDM achievement dimensions such as social resilience with access to education, health, housing and good social capital. Economic resilience through innovative ideas for developing community welfare through the one home one business program as well as ecological resilience through environmental quality and disaster response mitigation. The obstacles experienced in achieving independent village status are internal obstacles, namely the low quality of human resources and budget limitations, while external obstacles include low community participation and seasonal conditions. So the solution is carried out through intense communication between the village government and the community as well as schedule adjustments. Based on this research, researchers suggest that the achievements of independent villages in Jimbar Village can become a role model for local government policy to improve independent villages, improve the quality of human resources through various training programs and can become a reference for continuing research with deeper and different studies.